Peningkatan Produksi Kue Kering Remen Malang - Habibi, Soraya; Ginting, Andilopa; Aprilia, Reni; Fitri, Lailatul; Mukhyidin, Muhammad; Putra, Muhamad Alvin Surya (Jurnal PKM Manajemen Bisnis, 2024)
Cookies are a dry snack that has several flavors to choose from, from savory to sweet. This snack is usually served at big holiday celebrations such as Eid al-Fitr, Christmas, Chinese New Year and New Year. Indonesia, with a majority Muslim population, makes the pastry business a business that has good prospects. Community service partners, in this case students from the Development Economics study program, saw this prospect and started starting a dry cake business. The dry cake business he started started with the production of pineapple cakes and was offered through word of mouth. The market segment targeted is the lower middle segment. With the scope of marketing being limited to college friends and neighbors in the village where the partners live. The community service team saw that the partner's dry cake business startup had prospects for further development. The first thing the service team did was discuss with partners to identify problems found in their start-up business. From the problems identified, solutions are then planned. The results of the service activities include producing a logo design for the packaging label that is more attractive than previously not having a packaging label, the packaging used is more attractive, marketing has been expanded by utilizing social media Instagram, and product quality is better by using quality ingredients and delicious taste. more delicious.